DOES FINTECH PAYMENT GATEWAY EFFECTIVE IN IMPROVING INCOME OF MICROENTERPRISES IN SURABAYA? - Raihan Maramba Mahardhika Paripurna; Shochrul Rohmatul Ajija (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2019)
This study aims to examine the effect on the income of Micro and Small Enterprises (MSEs) in Surabaya. This study uses a quantitative research approach, Paired t-test and Independent t-test methods. The variables used are income, payment gateway, capital, and labor. Type of data source is primary data which is taken directly in the field by the author, namely MSEs who move in several sectors. The result is that the income of MSEs in Surabaya, the use fintech payment gateway, has a significant effect on increasing income by using the paired t-test method. Conversely, if use the Independent t-test payment gateway does not have a significant effect.